An examination of Post Implementation Success determinants of Enterprise Resource Planning: Insights from industrial Sector of Pakistan - Atif Gill; Dr. Arfan Shahzad; Dr. Subramaniam Sri Ramalu (International Journal of Supply Chain Management, 2019)
Enterprise Resource Planning (ERP) is an integrated software package which has been adopted extensively by numerous organization to survive in this technology-driven era. There are several studies that have investigated the critical factors for the success of ERP. However, some organizations are facing issues to get the desired benefits even after implementing ERP packages. The current study will focus on the key determinants that ensure the post-implementation success of ERP systems. This research is based on the Technology-Organization-Environment (TOE) theory. In this study, project management posited as a technological aspect, leadership involvement as an organizational aspect while external support depicted as an environmental aspect. An empirical analysis was done in the context of the industrial sector of Pakistan. The results depict the strong influence of project management, leadership involvement and external support on ERP post-implementation success. This research delivers practical as well as theoretical implications by providing an integrative model of critical factors for ERP success at Post-implementation phase.